The Determinants of Peer-to-Peer Accommodation Ecosystem in Malaysia - Kheng, Yeoh Khar; June, Sethela (International Journal of Psychosocial Rehabilitation, 2020)
Peer-to-peer (P2P) accommodation or sharing economy lodging services has emerged over a decade that reshaped the global tourism industry, notably Airbnb. The general objective of this study is to examine the relationship between the three determinants, namely transaction costs, Internet-based platforms, profitability, and peer-to-peer accommodation ecosystem in Malaysia, moderated by the consumer purchase behaviour. Survey method and data were collected using an intercept method from 200 peer-to-peer accommodation user in Malaysia. Through the robust analysis of Smart PLS, the study found support on the relationship between transaction costs and peer-to-peer accommodation ecosystem, as well as on the relationship between transaction internet-based platforms and peer-to-peer accommodation ecosystem. While, the relationship between profitability and peer-to-peer accommodation ecosystem is not supported. As for the moderating effects of consumer purchase behaviour on the relationship of transaction costs and peer-to-peer accommodation ecosystem, it is not supported. The moderating effects of consumer purchase behaviour on the relationship of internet-based platforms and peer-to-peer accommodation ecosystem, it is not supported. Nevertheless, the moderating effects of consumer purchase behaviour on the relationship of profitability and peer-to-peer accommodation ecosystem, it is supported. This implies that consumer purchase behaviour; itself is a critical factor leading to peer-to-peer accommodation ecosystem (commercial sharing). Limitations of the study and future research also being discussed.